IMPACT OF THE COVID-19 PANDEMIC ON CONSUMER BEHAVIOR DURING SOCIAL ISOLATION AND SUSTAINABLE CONSUMPTION: A PERSPECTIVE IN BRAZIL AND PORTUGAL - Severo, Eliana Andréa; De Guimarães, Julio Cesar Ferro; Soares, Tiago Bedin; Ahire, Kaila D. (Revista Gestão Organizacional, 2023)
Purpose: This study aims to analyze the impact of the COVID-19 Pandemic on consumer behavior in social isolation and sustainable consumption, from the perspective of the 2030 Agenda, given the perception of 2403 residents in Brazil and Portugal, through four research hypotheses. Method/approach: The methodology used was quantitative and descriptive research, through exploratory factor analysis and multiple linear regression. Main findings: The results highlight that all hypotheses were confirmed, and the most relevant relationship, that is, the most significant impact, occurred between the COVID-19 Pandemic and consumer behavior in social isolation, as well as differences in the perception of respondents between the Countries. Theoretical, practical/social contributions: Regarding the managerial and social contributions of the research, they allow managers and health professionals to have knowledge about the impacts of the COVID-19 Pandemic, assisting them in developing strategies to face the Pandemic. In addition to information for public policies at the regional and national le’vels to support cities and regions in facing the Pandemic. Originality/relevance: Another important contribution of the research is the availability of an analysis framework, which has been statistically validated (observable variables and constructs). In this context, the Framework proposed in the research can be replicated in different regional, national, and international contexts.